2010
DOI: 10.1515/cclm.2010.290
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin concentrations and iron homeostasis in preeclampsia

Abstract: Plasma iron concentrations are increased despite high hepcidin concentrations in PE. This might indicate a resistance to the iron-decreasing action of hepcidin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 14 publications
1
41
0
1
Order By: Relevance
“…This review reveals a significant paucity of studies assessing hepcidin during pregnancy. Ten human [47,48,49,50,51,52,53,54,55,56] and six animal studies [57,58,59,60,61,62] met the inclusion criteria with findings reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This review reveals a significant paucity of studies assessing hepcidin during pregnancy. Ten human [47,48,49,50,51,52,53,54,55,56] and six animal studies [57,58,59,60,61,62] met the inclusion criteria with findings reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Six of the ten human studies utilized a cross-sectional study design [47,48,49,50,51,52] and four were longitudinal [53,55,56,68]. Sample size for the human studies ranged from 19 [52] to 191 subjects [48].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations